Pengembangan Aplikasi Pembelajaran Kanji menggunakan MLKit Text Recognition, Text-to-Speech dan Kanji Alive API (Studi Kasus: Kun-Yomi pada JLPT N5-N3) - Firmanda Mulyawan Nugroho; Agi Putra Kharisma; Wibisono Sukmo Wardhono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Mobile App Learning Kanji is learning app that focus to learn Japanese Languange Provience Test (JLPT) at N5 to N3 levels. 5 Respondent give us the problem from interview we had held, that they were struggled to learn kanji, to solve that problem, we use Mobile App Pembelajaran Kanji. In its development, researcher use feature to give user list kanji from N5 to N3, feature to know the kanji's details like meaning, kun-yomi's writing, total stroke, reading with hiragana, example how to use it in everyday life, and kanjis's sounds using Text-to-Speech, all that detail data obtained from Kanji Alive API. Evaluation feature has quiz to know how much the user's knowledge. Support feature has MLkit Text Recognition to recognize the kanji with kamera and show meaning of that kanji. Result of this research in effectiveness side is all respondent give statement effective in aspect of learning, kanjis's meaning, and kanjis's example sentecence, but in evaluation aspect, 2 respondent want a enhancement and detailing. Usablity has result usefulness has 86.8 %, easy-to-learn has 81%, easy-to-use has 83.125% and satisfaction has 74.5 %.That result give us very agree point at first three aspect and agree at last point.